Towards a new paradigm: an examination of the interface between design and ergonomics through the use of case-study methods - Steven W. Garner (1988)
Both the designer and the ergonomist occupy important positions within our industrial society. Traditionally their contribution to this society has suffered from both public and professional misunderstandings regarding the role of each. To compound this issue both professions are undergoing radical changes in the light of a developing sociological, technological and commercial environment. This research is focussed on one aspect of this change; that is, the nature of a developing relationship between design and ergonomics. It presents this relationship as an interface and attempts to illuminate the richness and variety of design/ergonomic activity at this interface. Chapter Two presents an overview of what has been termed the 'parent' domains of design and ergonomics, while Chapter Three seeks to establish the validity of employing case-study methods for an illumination of the interface. This dwells upon the work of Thomas Kuhn and uses his notion of 'paradigms' to assist in the definition of a contemporary relationship. Chapters Four and Five present a thorough analysis of the sixteen case-studies used for the research. They provide evidence for viewing design/ergonomic activity as a widespread and increasingly independent phenomenon. This is shown to have implications for higher education as well as the professions of design and ergonomics.